2022
DOI: 10.1038/s41598-022-10435-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key genes in milk fat metabolism by weighted gene co-expression network analysis

Abstract: Milk fat is the most important and energy-rich substance in milk, and its content and composition are important reference elements in the evaluation of milk quality. However, the current identification of valuable candidate genes affecting milk fat is limited. IlluminaPE150 was used to sequence bovine mammary epithelial cells (BMECs) with high and low milk fat rates (MFP), the weighted gene co-expression network (WGCNA) was used to analyze mRNA expression profile data in this study. As a result, a total of 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Weighted gene co-expression network analysis (WGCNA) is a valuable R tool that integrates gene expression data with phenotypic information to identify key modules and hub genes associated with target traits. This approach effectively clusters genes exhibiting similar expression patterns into distinct modules, which are characterized by shared functions or pathways [40]. By leveraging plant life activities and high-throughput sequencing technology, WGCNA enables the acquisition of multiple expression traits and facilitates the construction of a scale-free network topology centered around pivotal regulatory genes [41].…”
Section: Introductionmentioning
confidence: 99%
“…Weighted gene co-expression network analysis (WGCNA) is a valuable R tool that integrates gene expression data with phenotypic information to identify key modules and hub genes associated with target traits. This approach effectively clusters genes exhibiting similar expression patterns into distinct modules, which are characterized by shared functions or pathways [40]. By leveraging plant life activities and high-throughput sequencing technology, WGCNA enables the acquisition of multiple expression traits and facilitates the construction of a scale-free network topology centered around pivotal regulatory genes [41].…”
Section: Introductionmentioning
confidence: 99%
“…The most significant SNP, rs133231370, corresponded to a nearby hub gene, ATP8A2, known for its involvement in lipid metabolism. Previously, ATP8A2 has been discussed for its role in milk fat synthesis in Holstein cattle [48]. This gene produces an ATPase protein responsible for transferring, or flipping, phosphatidylserine (PS) and phosphatidylethanolamine from the ectoplasmic to the cytoplasmic layers of the cell membrane lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…Palombo et al [14]discovered through GWAS analysis that PI4K2A is an important candidate gene for bovine milk fat metabolism. Mu et al [11] further identi ed the differential expression of the PI4K2A gene in high and low milk fat groups through transcriptomic analysis of BMECs. In this study, qRT-PCR detection revealed that the expression of the PI4K2A gene in cow mammary tissue was signi cantly higher than in other tissues, and the expression of the PI4K2A gene in both cow mammary tissue and BMECs was relatively constant.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, our group previously investigated the genomewide expression of mRNA transcripts in bovine mammary epithelial cells (BMECs) with high and low milk fat percentages by using comparative transcriptomics [10]. We performed a comprehensive analysis of mRNA expression pro le data using the weighted gene co-expression network analysis (WGCNA) and identi ed 15 candidate differential genes potentially regulating milk fat metabolism (Supplementary Table . 1) [11]. To further pinpoint and validate the most critical genes involved in milk fat synthesis in dairy cows, this study conducted tissue expression pro ling of the 15 candidate genes by using quantitative real-time PCR (qRT-PCR).…”
Section: Introductionmentioning
confidence: 99%